MAGNETIC RESONANCE IMAGING IN THE DIAGNOSIS OF JUVENILE IDIOPATHIC ARTHRITIS - A. K. Traudt; V. D. Zavadovskaya; T. V. Zhogina; Ye. I. Fedorova (Бюллетень сибирской медицины, 2015)
Juvenile idiopathic arthritis (JIA) are a group of socially significant diseases of childhood because of the high prevalence of a chronic nature, as well as a large percentage of early disability. JIA is a collection of diseases that have different start, course and outcome, as well as various etiologies, which emphasizes the difficulties in the diagnosis process in children. When this disease is progressive in nature, leads to loss of function of the musculoskeletal system, severe disability at an early age and, therefore, needs early diagnosis and adequate therapy appointment.Significant role in identifying pathology osteoarticular system belongs radiological methods and routine radiography remains the most widely used technique included in the classification criteria of the majority of rheumatic diseases. However, it is well known that secondary structural changes in the bones precedes roentgen period, and therefore the X-rays can not be regarded as a method of early diagnosis with articular syndrome. Widely introduced in recent years, magnetic resonance imaging (MRI) has more say in the assessment of capabilities of the joints, as in addition to assessment of bone allows quantitatively and qualitatively assess changes in the synovial membrane, articular cartilage, the presence and severity of inflammatory changes in the periarticular soft tissue and bone tissue. The data obtained using MRI may be used for diagnosis, prognosis, and monitoring response to treatment, including early stage disease.Nevertheless, despite the obvious opportunities MRI, this technique is not widely used, including the lack of clear diagnostic criteria for the disease, the lack of centralized research validated, standardized protocols for conducting MRI studies of children with articular syndrome. Thus, research is warranted to address a number of clinical and diagnostic aspects in JIA, in particular the development of the scoring system assessing the severity and progression of the disease.